2000
DOI: 10.1111/1467-8551.00175
|View full text |Cite
|
Sign up to set email alerts
|

Can Target Costing and Whole Life Costing be Applied in the Construction Industry?: Evidence from Two Case Studies

Abstract: Building on the results of a far-reaching action research project we discuss an attempt to introduce target costing in the UK construction industry. After examining some of the issues facing the UK construction industry, we examine the case for using target costing as a way of supporting supply-chain integration in view of an improvement of the level of profitability and quality of the industry. After presenting evidence from two pilot projects we propose some considerations on target costing and its applicabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
17

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 12 publications
(24 reference statements)
3
92
0
17
Order By: Relevance
“…Nicolini et al (2000) outline the limitations of implementing strategic-orientated approaches to cost in contexts where a lack of trust and transparency is deep-seated within the industry's culture and practices. The move towards availability contracting should provide the cooperative environment which is necessary for approaches such as TLC to work (Goldbach, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicolini et al (2000) outline the limitations of implementing strategic-orientated approaches to cost in contexts where a lack of trust and transparency is deep-seated within the industry's culture and practices. The move towards availability contracting should provide the cooperative environment which is necessary for approaches such as TLC to work (Goldbach, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, TLC deployment is hindered by use in tendering and aggressive bargaining as a tool to exploit commercial situations (Nicolini et al, 2000). Resistance to TLC can be internal to an organisation.…”
Section: Rq1mentioning
confidence: 99%
“…In construction and other capital intensive industries there is a further, more complex dimension that refers to longterm life cycle costs. Once cost modelling spans decades, instead of months or years, the issue is not only that of the availability and reliability of data, but also the compatibility of the timescale with the ever-shorter time horizons utilized by private and public corporations in their decision making processes, as well as the need to compare different economic and financial future scenarios [20]. Nicolini et al [20] showed through case study research in UK construction industry, the industry often operates without full understanding of costs throughout the supply chain, which changes with time.…”
Section: Whole Life Cycle Costmentioning
confidence: 99%
“…Once cost modelling spans decades, instead of months or years, the issue is not only that of the availability and reliability of data, but also the compatibility of the timescale with the ever-shorter time horizons utilized by private and public corporations in their decision making processes, as well as the need to compare different economic and financial future scenarios [20]. Nicolini et al [20] showed through case study research in UK construction industry, the industry often operates without full understanding of costs throughout the supply chain, which changes with time. Nicolini et al [20] found, most players in construction currently either develop prices through "top down" estimating based on rates for building elements or else can only price something once quotes have been received from the various subcontractors or materials suppliers involved in delivering a fixed design.…”
Section: Whole Life Cycle Costmentioning
confidence: 99%
See 1 more Smart Citation